An Overview of Push/Pull Factors of Political Participation in Nigeria - Muhammad Fuad Othman; Nazariah Osman; Isah Shehu Mohammed (Journal of International Studies, 2018)
This article overviews the push/pull factors of citizensâ€™ participation in Nigerian politics. Citizensâ€™ participation in state politics is both integral and an indispensable part of every political system and development. However, it is determined by numerous factors which are universal, but relative in terms of contexts. Such a participation is affected by many factors in Nigeria. The study uses secondary sources to collect data and perform qualitative analysis. The study is timely and significant in view of the critical roles where participation plays in shaping and influencing Nigerian politics, especially at the current moment when it is being characterized by apathy and participation on two ends. It is concentrated on an atmosphere of push and pull forces, negative and positive issues and developments, this environment is manipulated by elites/politicians. This needs a change for the better, to inculcate hope, overcome despair, anxiety as well as increased ethno-religious and electoral tensions.